2008
DOI: 10.1021/ie071660g
|View full text |Cite
|
Sign up to set email alerts
|

Foaming in Wet Flue Gas Desulfurization Plants:  The Influence of Particles, Electrolytes, and Buffers

Abstract: The objective of this work is to study the influence of particles, electrolytes, and buffers on the foaming ability of wet flue gas desulfurization (FGD) slurries. Foaming within this industrial process has been associated with a range of operational problems, as well as an increased degree of absorption. The foaminess of selected process parameters has been assessed, systematically, using laboratory-scale Bikerman experiments. Adipic acid alone, as well as a combination of small particles and an electrolyte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Therefore, nearly 5 mol SO2 mol IL −1 can be absorbed as a result of multiple-site interactions between the electronegative nitrogen atoms and the sulfur atom with positive charge in the acidic SO 2 . Note that Wang et al [19] reported a novel strategy for SO 2 . Compared with the interaction energies reported in [19], our results are relatively lower, which could be attributed to differences in the simulation model (in Wang et al [19], only the anion was considered, while in the present work the whole IL was included).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, nearly 5 mol SO2 mol IL −1 can be absorbed as a result of multiple-site interactions between the electronegative nitrogen atoms and the sulfur atom with positive charge in the acidic SO 2 . Note that Wang et al [19] reported a novel strategy for SO 2 . Compared with the interaction energies reported in [19], our results are relatively lower, which could be attributed to differences in the simulation model (in Wang et al [19], only the anion was considered, while in the present work the whole IL was included).…”
Section: Resultsmentioning
confidence: 97%
“…The second one is a π-hole interaction through the S atom in SO 2 as an electron acceptor and N atom in [Et 2 NEMim][Tetz] as an electron donor [32]. In the IL-1SO 2 complex, the S atom in SO 2 bonded to the N2 in [Tetz] − forms a π-hole interaction, while the two O atoms in SO 2 2.339 Å and 2.595 Å for N3⋯H2, O1⋯H5 and O3⋯H3, respectively. The fourth SO 2 has a larger effect on the first SO 2 and a smaller effect on the second and third SO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] Ionic liquids were found to be key absorbents, due to negligible volatility, high thermal and chemical stability, and tunable chemical properties, which have been widely used in gas separation. For instance, Han et al [7] first synthesized a base-functionalized IL, 1, 1, 3, 3-tetramethylguanidinium lactate (TMGL), and reported that it can effectively absorb SO2 from a simulated flue gas with high absorption capacity (0.978 mol SO2/mol TMGL) and high selectivity.…”
Section: Introductionmentioning
confidence: 99%